2002
DOI: 10.1007/s00420-001-0293-1
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and characterization of Bacillus cereus-like bacteria from faecal samples from greenhouse workers who are using Bacillus thuringiensis-based insecticides

Abstract: The methods applied have verified that the faecal isolate was identical to the B. thuringiensis isolate found in the biopesticide used. This is the first reported case of isolation of a bacterial biopesticide from human faeces. The biopesticide was shown to harbour and express enterotoxin genes. However, there is no evidence that this caused any adverse effects to the person from whom these bacteria were isolated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
20
0

Year Published

2002
2002
2012
2012

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 42 publications
1
20
0
Order By: Relevance
“…The genes coding for insect toxins are found primarily on large plasmids in B. thuringiensis (5), and in the laboratory, these plasmids can be lost or transferred horizontally to other bacilli (16,17,28,30,47); hence, a B. thuringiensis strain can be transformed into a B. cereus strain and vice versa. We have previously isolated B. thuringiensis from the feces of exposed persons (29), and in this study, we have shown that commercial preparations of B. thuringiensis subsp. israelensis contain the genes for and produce enterotoxins characteristic of B. cereus.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…The genes coding for insect toxins are found primarily on large plasmids in B. thuringiensis (5), and in the laboratory, these plasmids can be lost or transferred horizontally to other bacilli (16,17,28,30,47); hence, a B. thuringiensis strain can be transformed into a B. cereus strain and vice versa. We have previously isolated B. thuringiensis from the feces of exposed persons (29), and in this study, we have shown that commercial preparations of B. thuringiensis subsp. israelensis contain the genes for and produce enterotoxins characteristic of B. cereus.…”
Section: Discussionmentioning
confidence: 61%
“…Preparation of large plasmids was performed as described previously (30). All PCR amplifications were performed with a PTC-100 programmable thermal controller (MJ Research Inc.) as previously described (29). DNA was analyzed by horizontal gel electrophoresis (6 to 10 V/cm) in 0.5 to 1.0% agarose (SeaKem GTG) with 1ϫ Tris-borate-EDTA buffer (39) for 1.5 to 2 h. After electrophoresis, the gel was stained in 1 mg of ethidium bromide per ml for 5 to 10 min and destained in water.…”
Section: Designmentioning
confidence: 99%
“…Previous studies have shown growers to be exposed to Bacillus thuringiensis applied by spraying (19,26,27). The three biocontrol organisms included in this study (T. harzianum, Beauveria sp., and S. griseoviridis) were not observed to be a natural part of the airborne microbiota in the greenhouse.…”
Section: Discussionmentioning
confidence: 99%
“…Application of biocontrol products that contain MPCAs may increase growers' exposure to the microbial agent (9,19,26,27). The biocontrol product Supresivit contains the ascomycete Trichoderma harzianum (Rifai 1969) which belongs to the family Hypocreaceae.…”
mentioning
confidence: 99%
“…However, the role of CytK is not yet fully understood, since recent studies have indicated the existence of two variants of CytK (4, 10), the one (CytK2) having a lower toxicity than CytK1, which caused the severe food poisoning case. Also, commercially used B. thuringiensis strains have been shown to harbor genes for HBL, NHE, and CytK, and the expression of components of the three-component enterotoxins HBL and NHE has also been established (8,16,22).Since methods for identification of B. cereus-like bacteria in food and clinical settings do not distinguish between B. cereus and B. thuringiensis, the presence of B. thuringiensis in food and the role of this organism in food poisoning are not well described. The bacterium B. thuringiensis has only in one case been associated with food poisoning (15), although the bacterium has the same genetic potential for producing enterotoxins as B. cereus.…”
mentioning
confidence: 99%